A systematic scoping review of rodent models of catatonia: Clinical correlations, translation and future approaches - Mallien, Anne Stephanie; Brandwein, Christiane; Vasilescu, Andrei-Nicolae; Leenaars, Cathalijn; Bleich, André; Inta, Dragos; Hirjak, Dusan; Gass, Peter (Schizophrenia research, 2024)
Catatonia is a psychiatric disorder, which subsumes a plethora of affective, motor and behavioral symptoms. In the last two decades, the number of behavioral and neuroimaging studies on catatonia has steadily increased. The majority of behavioral and neuroimaging studies in psychiatric patients suggested aberrant higher-order frontoparietal networks which, on the biochemical level, are insufficiently modulated by gamma-aminobutyric acid (GABA)-ergic and glutamatergic transmission. However, the pathomechanisms of catatonic symptoms have rarely been studied using rodent models. Here, we performed a scoping review of literature available on PubMed for studies on rodent models of catatonia. We sought to identify what we could learn from pre-clinical animal models of catatonia-like symptoms, their underlying neuronal correlates, and the complex molecular (i.e. genes and neurotransmitter) mechanisms by which its modulation exerts its effects. What becomes evident is that although many transgenic models present catatonia-like symptoms, they have not been used to better understand the pathophysiological mechanisms underlying catatonia so far. However, the identified neuronal correlates of catatonia-like symptoms correlate to a great extent with findings from neuroscience research in psychiatric patients. This points us towards fundamental cortical-striatal-thalamocortical and associated networks modulated by white matter inflammation as well as aberrant dopaminergic, GABAergic, and glutamatergic neurotransmission that is involved in catatonia. Therefore, this scoping review opens up the possibility of finally using transgenic models to help with identifying novel target mechanisms for the development of new drugs for the treatment of catatonia.
Online verfügbar: 29. Juli 2023, Artikelversion: 18. Dezember 2023
Gesehen am 07.10.2024